THESIS TITLE: IDENTIFYING STRUCTURAL ELEMENTS IN A TEXT FOR A SPECIFIC PURPOSE - Shamsuddinova Ruqiyaxon; Abduraxmonov Toʻraxon (TADQIQOTLAR, 2025)
Introduction: When reading or writing for a specific purpose—such as academic study, business, or medical communication—it is essential to identify the structural elements of a text. These elements help the reader understand the organization, purpose, and key information within the text. Recognizing these structures improves both comprehension and effective communication.